Electoral Reforms for Accountability:: Improving Asset Disclosure and Campaign Finance in Bangladesh - Shahed, Md. Mahmudul Hasan; Rashid, Md Shahedur; Malek, Maria Binte; Shabab, Khaled Zubair (The Jahangirnagar Review, 2025)
This study explores the need for a transparent and consistent asset valuation methodology in Bangladesh's electoral process, specifically for the Holofnama, focusing on assets like land and gold. The absence of standardized valuation protocols leads to inconsistencies in asset declarations by election candidates. The research also proposes a voter-based adjustment to the Tk 25 lakh campaign spending cap, which currently varies across constituencies with differing voter populations. It also advocates for asset valuation guidelines modeled on industry standards, such as those set by the Bangladesh Jewellers Association (BAJUS) for gold and the Acquisition and Requisition of Inland Property Act 2017 for immovable assets. The study reveals that the uniform spending limit across constituencies is inadequate, especially in larger constituencies, where financial constraints may encourage unreported campaign funding. Findings suggest that adjusting campaign expenditure limits based on voter numbers and inflation and adopting standardized asset valuation practices for the Holofnama would enhance fairness and electoral integrity in Bangladesh.